Mitochondrial Dysfunction Is a Primary Event in Glutamate Neurotoxicity - Schinder, Alejandro F. (J Neurosci, 1996)
Excitotoxic neuronal death, associated with neurodegenerative disorders and hypoxic insults, results from excessive exposure to excitatory neurotransmitters. Glutamate neurotoxicity is triggered primarily by massive Ca(2+) influx arising from overstimulation of the NMDA subtype of glutamate receptors. The underlying mechanisms, however, remain elusive. We have tested the hypothesis that mitochondria are primary targets in excitotoxicity by confocal imaging of intracellular Ca(2+)([Ca(2+)](i)) and mitochondrial membrane potential (ΔΨ) on cultured rat hippocampal neurons. Sustained activation of NMDA receptors (20 min) elicits reversible elevation of [Ca(2+)](i). Longer activation (50 min) renders elevation of [Ca(2+)](i) irreversible (Ca(2+) overload). Susceptibility to NMDA-induced Ca(2+) overload is increased when the 20 min stimuli are applied to neurons pretreated with electron transport chain inhibitors, thereby implicating mitochondria in [Ca(2+)](i)homeostasis during excitotoxic challenges. Remarkably, ΔΨ exhibits prominent and persistent depolarization in response to NMDA, which closely parallels the incidence of neuronal death. Blockade of the mitochondrial permeability transition pore by cyclosporin A allows complete recovery of ΔΨ and prevents cell death. These results suggest that early mitochondrial damage plays a key role in induction of glutamate neurotoxicity.